2018
DOI: 10.1155/2018/8526190
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Functionalized Mesoporous Hollow SnO2 Nanofibers as a Targeting Drug Carrier to Improve the Antitumor Effect of Paclitaxel for Liver Cancer Therapy

Abstract: In this study, we prepared PTX-loaded mesoporous hollow SnO2 nanofibers conjugated with folic acid (SFNFP) for liver cancer therapy. According to SEM and TEM characterization, SFNF showed a mesoporous hollow structure. The average outer diameter was 200 nm, and the wall thickness was 50 nm. The DSC and XRD study showed that PTX in the channels of nanofibers was present in an amorphous state. The in vitro release experiments demonstrated that SFNF could efficiently improve the dissolution rate of PTX. Both in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…For instance, SnO 2 NP could induce human HCT116 and A549 cells to produce ROS in vitro , which leads to cell death ( Tammina et al, 2017 ); besides, it is found that SnO 2 NP treatment can cause HepG2 cells to occur Morphological changes and cytotoxic effects ( Roopan et al, 2015 ); it is also demonstrated that SnO 2 NP can induce oxidative stress in MCF-7 cells, prompting the cells to synthesize ROS, increasing H 2 O 2 levels, triggering lipid peroxidation, reducing glutathione and antioxidant enzymes levels, and finally causing cell damage ( Ahamed et al, 2018 ); Moreover, Lv found that SnO 2 nanofibers can not only reduce the cell activity of hepatocellular carcinoma SMMC-7721 but also induce apoptosis. Western blot detection found that the expression of Caspase-3, the apoptosis-related protein, was increased ( Lv et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SnO 2 NP could induce human HCT116 and A549 cells to produce ROS in vitro , which leads to cell death ( Tammina et al, 2017 ); besides, it is found that SnO 2 NP treatment can cause HepG2 cells to occur Morphological changes and cytotoxic effects ( Roopan et al, 2015 ); it is also demonstrated that SnO 2 NP can induce oxidative stress in MCF-7 cells, prompting the cells to synthesize ROS, increasing H 2 O 2 levels, triggering lipid peroxidation, reducing glutathione and antioxidant enzymes levels, and finally causing cell damage ( Ahamed et al, 2018 ); Moreover, Lv found that SnO 2 nanofibers can not only reduce the cell activity of hepatocellular carcinoma SMMC-7721 but also induce apoptosis. Western blot detection found that the expression of Caspase-3, the apoptosis-related protein, was increased ( Lv et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro dissolution study results show that SFNFP exhibited an 8.34 times higher dissolution rate compared to naked Paclitaxel, over a period of 5 minutes. While the cumulative release rate of pure Paclitaxel was only 16.77 ± 2.00% after 1h, a high dissolution rate of 80.00 ± 2.64% was observed from SFNFP [63]. The release profiles of Paclitaxel from the SFNFP followed Noyes-Whitney’s drug release profiles.…”
Section: Applications Of Nanofibers In Therapeutics Deliverymentioning
confidence: 98%
“…Nanoparticles are used directly and in nanofiber forms. Upon using nanoparticles with nanofibers, drug release time increases, and therefore makes it possible to load more drugs on both nanoparticles and nanofibers 167 . Fiber‐based DDSs use a variety of ionic, metallic, carbon, and paramagnetic nanoparticles and nanocarriers (virus, micelles, liposomes, and bacteria).…”
Section: Application Of Nanoparticles In Ddssmentioning
confidence: 99%